Age of acquisition and imageability: a cross‐task comparison. (14th November 2014) - Ploetz, Danielle M.; Yates, Mark
Abstract : Previous research has reported an imageability effect on visual word recognition. Words that are high in imageability are recognised more rapidly than are those lower in imageability. However, later researchers argued that imageability was confounded with age of acquisition. In the current research, these two factors were manipulated in a factorial design to assess their effect in a lexical decision task and a progressive demasking task. Across both tasks, there was a clear and robust effect of age of acquisition. In contrast, the imageability effect was only evident in the progressive demasking task. Both effects are explained within the connectionist framework in terms of network plasticity and semantic feedback activation.